Mesostructured Electroactive Thin Films Through Layer‐by‐Layer Assembly of Redox Surfactants and Polyelectrolytes. Issue 8 (20th May 2020) - Piccinini, Esteban; Ceolín, Marcelo; Battaglini, Fernando; Azzaroni, Omar
Abstract: Electroactive thin films are an important element in the devices devoted to energy conversion, actuators, and molecular electronics, among others. Their build‐up by the layer‐by‐layer technique is an attractive choice since a fine control over the thickness and composition can be achieved. However, most of the assemblies described in the literature show a lack of internal order, and their thicknesses change upon oxidation‐state alterations. In this work, we describe the formation of layer‐by‐layer assemblies of redox surfactants and polyelectrolytes that leads to the construction of mesoscale organized electroactive films. In contrast to thin films prepared with traditional redox polymers, here, the redox surfactant does not only allow the control of the film meso‐organization (from 2D hexagonal to circular hexagonal phases) but it also allows the control of the number and position of the redox centers. Finally, these films show high stability and a negligible structural deformation under redox‐state changes. Abstract : Meso‐organized Domains : The layer‐by‐layer assembly of polyelectrolytes and surfactants enables structural control of multilayers displaying meso‐organized 3D redox‐active domains. The approach exploits the dual role of surfactants as functional units, i. e .: redox active centers, and structural units, such as structure‐directing agents. The population of redox centers hosted into the film can be manipulated by co‐assembling electroactive and non‐electroactive surfactants. This strategy constitutes a straightforward technique to produce electroactive films with precise control over the spatial organization of their redox domains, even under dynamic electrochemical conditions.